2020
DOI: 10.1016/j.bbi.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Brain abnormalities in COVID-19 acute/subacute phase: A rapid systematic review

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 35 publications
3
86
0
6
Order By: Relevance
“…We found that white matter abnormalities was the most frequent neuroimaging pattern in patients with COVID-19 and neurological manifestations, which is consistent with a previous review (37). White matter-specific injuries was presented in a case series of six COVID-19 patients who exhibited an altered mental status (38).…”
Section: White Matter Abnormalitysupporting
confidence: 90%
“…We found that white matter abnormalities was the most frequent neuroimaging pattern in patients with COVID-19 and neurological manifestations, which is consistent with a previous review (37). White matter-specific injuries was presented in a case series of six COVID-19 patients who exhibited an altered mental status (38).…”
Section: White Matter Abnormalitysupporting
confidence: 90%
“…Nevertheless, a shortage of brain images on all patients might alter the results. Also, the deeper brain structures, cerebellum, and midline involvement were rarely reported [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review that included 26 neuroimaging studies, most of them case series of COVID-19 patients who underwent brain imaging examination due to neurological symptoms, found that 34% (124/361) of the cases presented brain lesions probably attributable to COVID-19 and among them, the most common finding was diffuse subcortical and deep white matter abnormalities. Other common findings, although less prevalent, were microhemorrhages, hemorrhages, and infarcts (Rita Egbert et al, 2020).…”
Section: Mechanisms Involved In Cognitive and Neuropsychiatric Manifementioning
confidence: 94%